Co-crystal sustained by π-type halogen-bonding interactions between 1,4-diiodoperchlorobenzene and naphthalene - Eric Bosch; Eric W. Reinheimer; Daniel K. Unruh; Ryan H. Groeneman (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The formation and crystal structure of a co-crystal based upon 1,4-diiodoperchlorobenzene (C6I2Cl4) as the halogen-bond donor along with naphthalene (nap) as the acceptor is reported. The co-crystal [systematic name: 1,2,4,5-tetrachloro-3,6-diiodobenzene–naphthalene, (C6I2Cl4)·(nap)] generates a chevron-like structure that is held together primarily by π-type halogen bonds (i.e. C—I...π contacts) between the components. In addition, C6I2Cl4 also interacts with the acceptor via C—Cl...π contacts that help stabilize the co-crystal. Within the solid, both aromatic components are found to engage in offset and homogeneous face-to-face π–π stacking interactions. Lastly, the halogen-bond donor C6I2Cl4 is found to engage with neighboring donors by both Type I chlorine–chlorine and Type II iodine–chlorine contacts, which generates an extended structure.